The effects of detergents on rice a teaching material for environmental education - Laurente, Elsie Paller 1943-
This investigation was undertaken to find out the effects of detergents on the growth and yield of rice. It is aimed at finding out the effects of detergents on the height, tillering capacity, flowering time, yield and fertility.